A Methodical Evaluation of Teachers’ Knowledge and Practices of Differentiation in Basic Schools in the Effutu Municipality of Ghana (International Journal of Scientific Research and Management (IJSRM), 2023)
Teachers’ knowledge of differentiation and how they practice differentiation was evaluated in fifteen (15) Basic Schools of the Effutu Municipality. The study was guided by two (2) research questions and two (2) hypotheses. The study adopted the Vygotsky (1978) socio-cultural learning theory as the theoretical framework. A qualitative research method was employed as the approach and a case study as the design for the study. Relying on a primary data, a multi-stage sampling method which involved purposive sampling and simple random sampling was used to select the samples. The analyses revealed that the teachers have very high knowledge with respect to strategies of differentiation. Also, the frequency of implementation of differentiation in the subject areas was very good as only 3.3% of the selected teachers do not implement it in any of the subject areas they teach. It was found the proportion of teachers who implemented differentiation in core subjects like Mathematics, English Language and Natural Science were not significantly different from those who do not. Though, the result was generally reassuring, the study made recommended that enhanced supervision, and continuous professional development training therein for improving the situation.